TINDAK PIDANA KORUPSI DITINJAU DARI HAM DI INDONESIA - Irwan Sapta Putra (LPPM Universitas Bina Bangsa, 2022)
This study discusses the problem of corruption related to human rights violations that exist in Indonesia, Human Rights are a set of rights that are inherent in the nature and existence of humans as creatures of God Almighty and are His gift that must be respected, upheld and protected by state, law, government, and everyone for the sake of honor and protection of human dignity. Eradication of Corruption Crimes carried out by the Corruption Eradication Commission (KPK) is currently being intensively carried out by the KPK, this can be seen from electronic media news, both printed and online. From this news, we can see together that the KPK has never stopped carrying out its duties in eradicating corruption in Indonesia. Even though many perpetrators of corruption have been arrested by the KPK, this does not necessarily eliminate the crime of corruption, even though every year there are criminals who are arrested by the KPK. The arrests of perpetrators of criminal acts of corruption by the Corruption Eradication Commission, ranging from high-ranking state officials such as the Minister and Chairman of the DPR RI to law enforcers (police, prosecutors, judges and advocates) as well as regional officials such as governors, mayors and regents and DPRD members also did not escape the arrests. by the KPK. The crime of corruption is a crime that can be categorized as a crime of gross human rights violation because the impact caused by these criminal acts can disrupt the country's economy and also hinder the development of the country and even these crimes can also disrupt the world economy